Urban stream ecology: drives of fish assemblage structure and ecological guidelines for rehabilitation - Cruz, Lorenna Campos (2019)
The several impacts of urbanization on natural environments tend to increase with the growth of the global population living in urban areas. Changes in hydrology, geomorphology and water quality are described in urban streams. We know that physical habitat structure has been recognized as a relevant factor in the distribution and structuring of fish assemblages on streams. In this way, variations related to changes in channel morphology, depth and type of substrate, for example, are responsible for restructuring fish communities and thus reflect the basins current conditions. However, the response of ichthyofauna to urbanization, particularly in neotropical streams, has been poorly explored. This elucidates the importance of studies that increase the understanding of the relationship between biota and the urban environment. In addition, this knowledge is necessary to indicate appropriate conservation and management actions that can provide improvements in these ecosystems. In this context, this dissertation aims to expand ecological studies in tropical urban streams by investigating the factors that structure fish assemblages in an urban basin (Chapter 1) and, based the main stress factors for fish biodiversity, discuss guidelines for the conservation and management of the Ribeirão Vermelho basin in Lavras, Minas Gerais (Chapter 2). To do so, were collected in 16 streams physical habitat variables, physical-chemical variables and their ichthyofauna. Results revealed the importance of variables linked to habitat complexity and basin connectivity to species richness. Additionally, riparian vegetation was the main drive of fish assemblage explaining 78% of abundance variation. We identify higher dominance of exotic species Poecilia reticulata and tendency of biotic homogenization in the basin that expand from deeper areas of the urban shadow to periphery. In response to the negative effects of urbanization in the basin, priority areas for the creation of greenways were indicated. In addition to this, three sites were identified to open buried streams and discussed future actions to mitigate the impacts of urbanization in the basin. Our results emphasized the importance of evaluating physical and ecological variables of streams besides water pollution. And support practices that avoid canalization, promoting connective along streams network and remove artificial structures in urban basins.